POTENSI PENGEMBANGAN INDUSTRI TEPUNG IKAN DARI LIMBAH PENGOLAHAN MAKANAN TRADISIONAL KHAS PALEMBANG BERBASIS IKAN - Harris, Helmi; Efreza, Dandy; Nafsiyah, Ikromatun (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
Palembang is famous for tradisional food from fish , such as pempek, kemplang, tekwan, bakso, model, siomay, otak-otak and the other tradisional foods. The main raw material for these traditional foods are fish gaging, while the remining (such as liver, bones, heads, fins, and viscera) is considered as part that has no economic value anymore and are considered as waste. In fact, from these fish contain the nutritional value is still high enough , when processed in such a way to produce marine fish mealproducts that have high economic value and are required in the manufacture of animal feed and fish pellet production. In this area there is no productive enterprise which is specially engaged in the utilization of fish waste from the processing of Palembang traditional foods based fish into fish meal products scale home industry. The possibility of this is due to the unavailability of data and information adequate technical and economical. In order to meet the needs that this research was conducted. The goals of these research are to produce the marine fish meal wich have hight quality of Indonesia Standard National (SNI) and to produce the recommendation of bussinis feasibility analysis . The yield of this research showed that the fish meal was produced has included the third quality of Indonesia Standard National (SNI). Judging from the business feasibility analysis, wich includes site selection, availability of raw materials, production processes, marketing, impact to the environtment and bussinis analysis (B/C Ratio = 1.33, BEP = 20.079 kg, ROI = 7,87 % and PBP = 12,71 mounths), the establishment of this marine fish meal factory is feasible to run.